Optimal conditions required for influenza A infection‐enhanced cross‐priming of CD8+ T cells specific to cell‐associated antigens. Issue 9 (10th September 2013) - Wei, Joe; Waithman, Jason; Xiao, Kun; Oveissi, Sara; Chen, Weisan
Abstract : Dendritic cells can take up exogenous tumor antigens and present their antigenic epitopes to CD8 + T cells (TCD8+ ), a process called cross‐presentation. Cross‐presentation is especially important in antitumor immunity because tumor cells, although carrying tumor antigens, do not activate naive T cells efficiently because of a lack of co‐stimulatory molecules. Our group has recently shown that influenza A virus (IAV) infection of allogeneic cells lead to enhanced cross‐priming of TCD8+ specific to cellular antigens. To develop this into a potential vaccine strategy, in this study, we have systematically investigated the numbers of allogeneic cells infected by IAV, IAV doses and their infectious activity, the length of in vitro infection and other associated factors. We have defined the optimal immune‐enhancing conditions and we have also shown in vivo that such enhanced cross‐priming did lead to enhanced tumor protection. The knowledge should be useful for developing more robust cancer vaccine.